Motivação do serviço público: influências sobre o ajuste indivíduo-organização e o comportamento de cidadania organizacional - Oliveira, Jefferson Menezes de (2019)
The present study aimed to analyze the influences of Public Service Motivation (PSM) on Person-Organization Fit (P-O Fit) and Organizational Citizenship Behavior (OCB) from the perspective of public servants working in federal educational institutions, considered strategic in the formation of citizens, promoting social equality and knowledge production. In this sense, a framework of analysis related to the interactions between the constructs addressed was proposed for the Brazilian context. As a result, an exploratory quantitative research was carried out, using a survey administered to individuals belonging to the target population - public servants of the teaching and technical-administrative careers of the federal educational institutions. Firstly, the processes of translation, adaptation and validation of the measurement scales related to the constructs addressed in the study were carried out. It was confirmed at this stage of the research the hypothesis that PSM has four dimensions of analysis in the Brazilian context (attraction to public service, commitment to public values, compassion and self-sacrifice), such as the international scale used as reference. In the sequence, the study carried out the analysis of structural models related to the interactions between PSM, P-O Fit and OCB. As a result, from the confirmatory factorial analyzes, the hypotheses were confirmed: the PSM positively influences the perceived P-O Fit; PSM positively influences OCB and; the P-O Fit positively influences the OCB. Finally, the hypothesis was confirmed that the positive influence of the PSM on the OCB, besides being direct, is also indirect and mediated by the perception of P-O Fit. These results indicate that individuals who are motivated for public service, that is, those who intend to perform a meaningful public service to society and the country, committed to public values, with compassion and willing to self-sacrifice tend to be compatible with your organization (public) regarding the congruence of values (perception of P-O Fit) and they are inclined to the manifestation of OCB in relation to co-workers and the organization they serve. Compared to the other relationships, it was identified that the direct influence of PSM on OCB was the most expressive. On the other hand, the indirect relation between PSM and OCB, through P-O Fit, although positive, corresponded to a partial mediation of smaller magnitude. In short, in addition to increasing knowledge about PSM manifestation and dimensionality among Brazilian public servants, this research explored their influences on perceptions and behaviors considered essential for organizational performance, confirming the hypotheses established.